DAPIC Problem-solving Process Towards Elementary Students’ Statistical Literacy - Diana Noviani Khakiki; Mohammad Faizal Amir (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Statistical literacy emphasizes the ability to read, interpret, understand, communicate, and critically analyze information data in the current century. Students' statistical literacy skills in elementary schools are considered insufficient. The reason is the limited problem-solving process on statistical literacy material. This research is to solve problems regarding elementary school students' statistical literacy by using the DAPIC problem-solving process (Define, Assess, Plan, Implement, and Communicate). An experimental method with pretest-posttest control group design was used on 38 elementary school students. The instrument used was a statistical literacy test analyzed using the Aiken V formula. The results of the study provided an average N-Gain value in the moderate category, which is less than equal to 0.3-0.7. The Wilcoxon test shows a value of 0.002, so there is an average difference between the two classes. Thus, the DAPIC problem-solving process positively impacts elementary school students' statistical literacy.